Determination and precision of otolith growth zone estimates of Electrona antarctica in the Southern Kerguelen Plateau region in the Indian sector of the Southern Ocean. (April 2020) - Zhu, Guoping; Duan, Mi; Wei, Lian; Trebilco, Rowan; Bestley, Sophie; Walters, Andrea
Abstract: Antarctic lanternfish ( Electrona antarctica ) is the dominant mesopelagic fish species in the Southern Ocean. It is the most common myctophid occurring south of the Antarctic Polar Front, and an important component of Southern Ocean food webs, both as a zooplankton predator and as a major prey item for higher predators. Despite its importance, there are major gaps in current understanding of the life history of E. antarctica, with previous ageing studies having produced inconclusive results, hampering our understanding of the population structure in this species and its role in marine ecosystems. This is particularly relevant around the Kerguelen Plateau, a highly productive region in the Indian sector of the Southern Ocean, where E. antarctica is a key mid-trophic level species. The present study took advantage of mesopelagic sampling efforts in the southern Kerguelen Plateau region on the 2015–2016 Kerguelen Axis study, and enumerated growth zones in the otoliths of a sample of 100 E. antarctica collected during the voyage. Growth zones were counted using both sectioned and whole otoliths and the precision of estimates was estimated by repeat counts. The estimated number of growth zones in the sectioned otoliths of E. antarctica (standard length 53–97 mm) ranging from 2 to 9. The average coefficient of variation (CV) and average percentage error (APE) for the estimated growth zones were 6.78% and 4.51%, respectively based on counts of sectioned otoliths. The number of growth zones in sectioned otoliths is positively related to weight of otolith and standard length of fish. The results presented here can inform future work on age structure and life history of E antarctica in the Southern Ocean as understanding of the nature of growth rings improves.